Pemberdayaan Masyarakat Melalui Pelatihan Pupuk Kompos Di Desa Surau - Afni Mujiarti; Fifian Permata Sari; Wilda Oktantika; Aisyah Destrini; Arya Damar; Hengky Saputra (-, 2026)
Surau Village has the potential to utilize organic waste, particularly dry leaves, which has not been optimally managed and may contribute to environmental pollution. This community service program aimed to empower the community through compost fertilizer training as an effort to manage organic waste and improve soil fertility. The methods participatoy employed included socialization, educational counseling, demonstrations, hands-on practice, and participant evaluation. The training utilized dry leaves and other organic materials that were readily available in the local environment. The results showed that participants gained knowledge and practical skills in processing organic waste into compost fertilizer and developed greater awareness of environmentally friendly waste management. This program is expected to be implemented sustainably to reduce the volume of organic waste, enhance soil quality, and support the creation of a cleaner, healthier, and more productive village environment.